Modelling the thermal decomposition of 3,4,5-trihydroxybenzoic acid using ordinary least square regression - Alberti, A.; Granato, D.; Nogueira, A.; Mafra, L. I.; Colman, T. A. D. [UNESP]; Schnitzler, E. (Univ Putra Malaysia Press, 2016)
Thermalgravimetric analysis and differential thermal analysis were employed to study the thermal behavior of gallic acid using regression models. Data were subjected to ordinary least square regression models and results showed that thermal decomposition occurred in three main steps with two endothermic peaks and two exothermic peaks due to oxidation process. The dehydration started at 74 degrees C in a single step until 107 degrees C. After that, the anhydrous compound was stable until 210 degrees C, when the decomposition of organic matter occurred in two consecutive steps. Regression models based on a first-order kinetic of gallic acid decomposition were proposed and equations were deemed statistically significant (p<0.05) and explained suitably the phenomenon. Differential scanning calorimetry (DSC) allowed the determination of the enthalpy of the main events and the Flynn-Wall-Ozawa non-isothermal method was used to investigate the activation energy of decomposition process that was found to be 150.31 kJ.mol(-1). (c) All Rights Reserved
Keywords: Phenolic compounds; TG; DSC; Kinetics; Regression